Evaluating Muscle Activity During Work With Trackball, Trackpad, Slanted, and Standard Mice - Yasser Labbafinejad; Mansour Eslami-Farsani; Saber Mohammadi; Mohamad Sadegh Ghasemi; Mahnoush Reiszadeh; Naser Dehghan (Iranian Rehabilitation Journal, 2019)
Objectives: Mouse is one of the most important data entry devices for computers. Undesirable and prolonged postures during work with the computer mouse increase workload, muscle aches and upper extremity musculoskeletal disorders. The present study aimed to evaluate and compare muscle activity during the use of 4 types of mouse, including trackball, trackpad, slanted and standard by Electromyography (EMG). Methods: This experimental study included 15 subjects (7 men and 8 women). The electrical activity of EDC, ECU, ECR, FDS, PQ, and FDL muscles was recorded by EMG while performing a standard task with each mouse. The order of using each mouse was randomized. The obtained results were analyzed by SPSS using the measures of central tendency, Friedman’s test, and Independent Samples t-test. Results: The results of assessing the electrical activity level of muscles suggested no statistically significant difference in the recorded EMG between FPL, FDS, and PQ muscles while working with the 4 mice. The electrical activity reduced in EDC, ECR, and FPL muscles with the use of slanted mouse, compared to that of other mice (P<0.05). Discussion: There was no significant differences between the electrical activity of FDS, FPL, and PQ muscles during work with the studied mice. Furthermore, the activity of EDC, ECR, and FPL muscles reduced during work with a slanted mouse, compared to the other types. The habit of using a new mouse can affect the level of muscle activity; thus, the use of a slanted mouse may reduce the incidence of musculoskeletal disorders in the wrist and hand of users in the long run.